Outcomes of sutureless aortic valve replacement versus conventional aortic valve replacement and transcatheter aortic valve replacement, updated systematic review, and meta‐analysis. Issue 12 (6th October 2021) - Kim, Kevin S.; Makhdoum, Ahmad; Koziarz, Alex; Gupta, Saurabh; Alsagheir, Ali; Pandey, Arjun; Reza, Seleman; Um, Kevin; Teoh, Kevin; Alhazzani, Waleed; Lamy, André; Yanagawa, Bobby; et al.
Abstract: Background: Sutureless aortic valve replacement (SuAVR) is an alternative to surgical aortic valve replacement (SAVR) and transcatheter aortic valve replacement (TAVR). This study compares the effectiveness of SuAVR to SAVR and TAVR. Methods: We searched MEDLINE and EMBASE from inception to July 2021 for studies evaluating SuAVR, SAVR, and TAVR in adults with aortic stenosis. We performed screening, full‐text assessment, data collection, and risk of bias evaluation independently and in duplicate. We evaluated risk of bias using by Cochrane and CLARITY's tools, and certainty in evidence using the GRADE framework. Data were pooled using a random‐effects model. Results: We identified one randomized and 78 observational studies ( n = 60, 689; SuAVR vs. SAVR = 39, 171, vs. TAVR = 21, 518). All studies were at high or unclear risk of bias, with very‐low certainty in effect estimates. Compared to TAVR, SuAVR demonstrates no significant difference in mortality at 30‐days (odds ratio [OR]: 0.52, 95% confidence interval [CI: 0.85, 1.16], I 2 = 0%), but decreased odds at 2‐years (OR: 0.39, 95% CI [0.17, 0.88], I 2 = 0%). SuAVR also reduced odds of mild paravalvular regurgitation (OR: 0.11, 95% CI [0.06, 0.21], I 2 = 50%). Compared to SAVR, SuAVR was associated with a similar mortality at 30‐days (OR: 0.99, 95% CI [0.85, 1.16], I 2 = 0%) and 2‐years (OR: 0.99, 95% CI [0.43–2.30], I 2 = 7%). SuAVR significantly increased odds of permanent pacemaker implantation (OR: 2.5, 95% CI [2.25, 2.77], I 2 = 0%). Pooled effect estimates were consistent with results from the randomized trial comparing SuAVR and SAVR. Conclusion: Based on very‐low quality evidence, SuAVR is associated with similar short‐ and midterm outcomes compared to TAVR and SAVR. Comparative randomized data with long‐term follow‐up are required to clarify the role of SuAVR.